Promotion of US private investment - Dietmar Haubold (Intereconomics, 1971)
The Overseas Private Investment Corporation (OPIC) has been officially in business since January 19, 1971. Its major purpose is to reorganise and widen the scope of programmes for the promotion of US private investment overseas in developing countries.
Keywords: 330; Development Policy